The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1472-765x.2002.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of faecal Lactobacillus populations in experimental animals from different breeding facilities and possible consequences for probiotic studies

Abstract: Aims: The effect of probiotic lactobacilli is likely dependent on the indigenous Lactobacillus strains in the intestinal tract. Since a substantial number of probiotic studies is performed in rodents, we compared the Lactobacillus strains of different rat and mouse populations in three animal facilities. Methods and Results: SDS-PAGE and 16S rDNA analysis of cultured faecal lactobacilli revealed that different Lactobacillus strains were detected in genetically similar Wistar rats bred at different locations. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Thus, the interindividual differences in intestinal repertoire could reflect differences in current antigenic exposure between rats or reflect the end result of sequential accumulation of small differences in the level of antigen exposure over time. Such differences are likely to be small at any one time‐point: studies of intestinal flora suggest some effect of genetics, but a strong effect of environment, such that animals from the same source had very similar flora 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interindividual differences in intestinal repertoire could reflect differences in current antigenic exposure between rats or reflect the end result of sequential accumulation of small differences in the level of antigen exposure over time. Such differences are likely to be small at any one time‐point: studies of intestinal flora suggest some effect of genetics, but a strong effect of environment, such that animals from the same source had very similar flora 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Differences in composition of the Lactobacillus flora might also be due to genetic factors (Tannock et al ., 1994), age and intestinal location (Lu et al ., 2003), ecological factors such as diet and lifestyle (Tannock et al ., 1994) and even the type of housing (De Waard et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1983) from conventional and SPF mice were L. johnsonii . Recently, it was reported that L. johnsonii , L. murinus and L. reuteri were detected predominantly in faecal samples from SPF mice by 16S rDNA sequences analysis (De Waard et al. 2002).…”
Section: Discussionmentioning
confidence: 99%